Clinical and Radiological Analyses of Anterior Cervical Discectomy and Fusion Involving One to Three Levels without Additional Plate Fixation: A Single-Center Experience - Romagna, Alexander; Schwartz, Christoph; Christopher, Reuben; Geroldinger, Martin; Dinzenhofer-Kessler, Dana; Schul, David; Tomasino, Andre (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
This study aimed to evaluate clinical and radiological outcomes of patients who underwent anterior cervical discectomy and fusion (ACDF) without additional anterior plate fixation.A retrospective, single-center analysis was conducted. Clinical outcomes were assessed by the Visual Analog Scale (VAS) scores, Neck Disability Index (NDI), and Odom's criteria. Radiological outcomes were evaluated based on changes in segmental disc height (subsidence), and Cobb angle by X-rays. Fusion was defined as a consistent distance between spinous processes.The study population consisted of 98 patients (mean age of 55.8 years) with a follow-up of 22.1 months. Procedures included 55 one-level, 33 two-level, and 10 three-level surgeries. The study results demonstrated good clinical outcomes, with statistically significant reductions in NDI scores with notable improvements in VAS (p < 0.001). Radiologically, we recorded a subsidence and reduction in Cobb angle of 1.6 mm/2.2 degrees in one-level, 3.8 mm/3.0 degrees in two-level, and 2.5 mm/2.4 degrees in three-level surgeries, respectively. Complete postoperative fusion was recorded for 86.7% patients, comprising rates of 87.3% for one-level, 90.9% for two-level, and 70.0% for three-level procedures. No revision surgery had to be performed.ACDF without additional plating appears to be an effective procedure for the surgical treatment of single- and multilevel degenerative cervical disease with good clinical outcome.
Keywords: ACDF; cervical discectomy; Cobb angle; fusion; plating